Spiritual contestations: the violence of peace in South Sudan - Pendle, Naomi Ruth (Religion in transforming Africa, 2023)
A fresh perspective on conflict and peace-making that highlights the cosmologies and invisible entities that state, society and religious authorities draw on to claim or reclaim legitimacy and control.